PENGARUH SOCIAL MEDIA MARKETING, LOKASI, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA CAFÃ‰ DEGREE DENPASAR - Ida Ayu Tripuspita; IA Cynthia Saisaria Mandasari; Ade Ruly Sumartini (Warmadewa Management and Business Journal (WMBJ), 2023)
Customer satisfaction is the level of customer feelings after comparing what is received and expectations, where a customer will feel satisfied with the value provided by a product or service that has been used before. The phenomenon that occurs in this study is that there are complaints from customers who do not get satisfaction, which causes a decrease in the number of visitors who come. The purpose of this study was to determine the relationship and influence of social media marketing, location, and service quality on customer satisfaction. This type of research is an empirical study of CafÃ© Degree in Denpasar. The sampling technique used was slovin, so the sample in this study was 99 respondents. The data analysis technique used is multiple linear regression where the independent variables are social media marketing, location, and service quality while the dependent variable is customer satisfaction. The results of the study show that social media marketing, location, and service quality simultaneously have a significant effect on customer satisfaction. Meanwhile, social media marketing, location, and service quality individually have a positive and significant effect on customer satisfaction.